Pengaruh Influencer Media Sosial dan Iklan Digital Terhadap Motivasi Belanja Impulsif Gen Z - Kunta Ramadhan Ridwan Putra; Iqsan Dinata; Marcello Armando; Fikri Rizki Utama (Indo Publishing, 2025)
This study aims to analyze the influence of social media influencers and digital advertising on the impulsive buying motivation of Generation Z. A quantitative approach was applied, involving 80 respondents selected through purposive sampling. Data were collected using a questionnaire and analyzed with multiple linear regression. The results show that both social media influencers and digital advertising have a positive and significant effect on impulsive buying motivation, both partially and simultaneously. The coefficient of determination (R²) of 0.327 indicates that these variables explain 32.7% of impulsive buying motivation. This study highlights the strong role of digital marketing strategies in shaping impulsive buying behavior among Generation Z.